(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
Congenital goiter is a very uncommon cause of neonatal neck mass. Administration of antithyroid drugs or radiation exposure during pregnancy may result in reduced synthesis of thyroxine and cause congenital goiter with or without thyroid dysfunction. We report a case of a full term, newborn male baby who had normal thyroid functions but was born with a neck swelling and no apparent abnormalities. Maternal investigations for thyroid function tests were found normal as well. Bangladesh J. Nuclear Med. 25(2): 121-124, 2022